The Courtly Strategy of Speech Behavior of a Communicative Sadist - Kseniia Taranenko (Психолінгвістика)
The article is devoted to the analysis of mechanisms of the courtly strategy of speech behavior as an expression of communicative sadism. The research was conducted in the context of psycholinguistics at the intersection of semantics, linguistic pragmatics and communicative linguistics. Considerable attention is paid to the essence, nature and characteristics of the phenomenon of communicative sadism, as well as the importance of studying this phenomenon as a variety of mental violence. A comparative analysis of foreign and domestic publications devoted to the study of aggression and violence in communication was carried out. The concepts of verbal aggression and communicative sadism were delimitated in detail and scientifically substantiated.